2016
DOI: 10.1007/s13105-015-0451-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of mycophenolate mofetil against nephrotoxicity and hepatotoxicity induced by tacrolimus in Wistar rats

Abstract: Tacrolimus (TAC), a calcineurin inhibitor (CNI), is clinically used as an immunosuppressive agent in the transplant recipient; however, the use of TAC is greatly limited by its nephrotoxicity and hepatotoxicity. Mycophenolate mofetil (MMF), an inhibitor of the purine synthesis, has been used in combination with many immunosuppressive drugs such as TAC. The association TAC/MMF was used in organ transplantation to increase the efficiency and reduce acute rejection rates, but the effects of MMF on TAC-induced kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…HK2 and RPTEC/TERT1 cells were treated with CyA and FK506 (10 μM each) for 6 and 24 h, respectively. The dose of 10 μM (CyA 12 μg/mL, FK506 8 μg/mL) is comparable to other studies [17,[39][40][41][42][43] and was identified in dose-response experiments, where HK2 cells were treated with various concentrations of CyA and FK506 (0.1-1000 μM), and 10 μM reflects the lowest dose that yielded a statistically significant decrease in proliferation by at least 20% (Supporting Information Fig. 1).…”
Section: Cni Induces Transcription Of Complement Factors But Reduces supporting
confidence: 78%
See 1 more Smart Citation
“…HK2 and RPTEC/TERT1 cells were treated with CyA and FK506 (10 μM each) for 6 and 24 h, respectively. The dose of 10 μM (CyA 12 μg/mL, FK506 8 μg/mL) is comparable to other studies [17,[39][40][41][42][43] and was identified in dose-response experiments, where HK2 cells were treated with various concentrations of CyA and FK506 (0.1-1000 μM), and 10 μM reflects the lowest dose that yielded a statistically significant decrease in proliferation by at least 20% (Supporting Information Fig. 1).…”
Section: Cni Induces Transcription Of Complement Factors But Reduces supporting
confidence: 78%
“…The same CyA concentrations (4-40 μg/mL) yielded a G1 and G2/M-phase arrest in LLC-PK1 renal tubule cells [41]. Kim et al [17] used 30 μg/g CyA to induce CIN in mice after 1-4 weeks of treatment, and up to 400 μg/g FK506 was used to induce nephrotoxicity in rats [39]. All these studies, except that of Kim et al, used time periods of 24-72 h, which is similar to our experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…This damage was associated with an increase of DNA fragmentation [2]. Other results suggest that coadministration MMF with tacrolimus protects the liver and kidney against tacrolimus toxicity via an antioxidant process [5]. We have not confirmed the mechanism of action, since that was not the goal of the current study; however, we revealed that the regimen that include MMF increased As and lowered Se level in renal transplant recipients, which seems to be unfavorable in aspect of function of transplanted organ.…”
Section: Discussioncontrasting
confidence: 54%
“…This is an immunomodulatory drug that inhibits inosine monophosphate dehydrogenase (IMPDH). The drug inhibits the proliferation of T and B cells [2][3][4][5]. MMF is mostly codrug with calcineurin inhibitors to prolong allograft function; it is believed that MMF exhibits antioxidant properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is an important trace element that serves as a structural ion in superoxide dismutase (SOD), an antioxidant enzyme that reduces oxidative stress [1]. Our results suggest that MMF evidently increased the level of Cu in blood, which may be associated with the fact that MMF inhibits ROS production by increasing the activity of Cu/Zn SOD [11]. Our findings correlate with those of the study of Kaminska et al [16], who found Cu levels to be significantly higher in blood serum of renal recipients who used MMF than in patients not using MMF [16].…”
Section: Discussionmentioning
confidence: 74%